WAYS TO IMPROVE THE USE OF FINANCIAL RESOURCES OF THE ENTERPRISE - Shukurova Bibigaisha Maksutovna; Bukharbayev Shynybek; Kalaganova Nursulu; Urazgalieva Marzhan Abdeshevna; Kabakbayev Akhan Satbaevich (Academic Journal of Physical and Chemical Sciences, 2020)
Identifying the sources of financial resources will help target the use of financial resources. жағдйы Sources of financial resources of the enterprise are usually considered shares. The policy of forming financial resources makes it possible to assess how effectively they are used. As a result of the analysis, the flexible relationship between accounts receivable and payable, capital and debt capital is calculated as a reasonable financial policy of the company. As a result of the analysis of the financial resources of LLP "TTT", we can see that the size of revenues increased in line with the annual growth of the assets and cash flows of the enterprise.